1996
DOI: 10.1063/1.362417
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration in isolated aluminum vias probed by resistance changes and 1/f noise

Abstract: Articles you may be interested inThe effect of current density and stripe length on resistance saturation during electromigration testing 1/f noise and high-resolution resistance measurements have been performed in isolated aluminum via interconnects under electromigration stress. The test structures had a volume of roughly 1 m 3 and a resistance of 0.1 ⍀ with an internal TiN diffusion barrier. The 1/f resistance noise of the vias was found to be larger than the 1/f noise in the connecting aluminum runners due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…From figures 9 and 10, it is envisaged that all the curves are nearly linear at the early stage of the electromigration where the crack begins to develop. This agrees with many experimental reports [14,[19][20][21][22]. For longer time, the resistance increases non-linearly and rapidly.…”
Section: Resultssupporting
confidence: 92%
“…From figures 9 and 10, it is envisaged that all the curves are nearly linear at the early stage of the electromigration where the crack begins to develop. This agrees with many experimental reports [14,[19][20][21][22]. For longer time, the resistance increases non-linearly and rapidly.…”
Section: Resultssupporting
confidence: 92%
“…It has also been observed that, to obtain a stationary 1/f 2 reading, one has to allow the system to reach equilibrium during a few hours typically. However, for high T and j , where noticeable EM occurs, it has for example been shown that a long-term mass-transport-based drift (up to several hours) of the resistance is observed, which generates a 1/f 2 spectrum as well [74][75][76][77]. An example is shown in figure 10.…”
Section: Em Lf Noise: Phenomenologymentioning
confidence: 99%
“….) in the metal film [74,78], since it is a sensitive function of the current distribution [10]. It is also the dominant LF noise in metal films with small physical size Figure 10.…”
Section: Em Lf Noise: Phenomenologymentioning
confidence: 99%
See 1 more Smart Citation
“…The flicker noise magnitude will increase as the extent of voiding in metal lines increases. 4 However, the gradient of the noise spectra will most likely remain at one unless there is significant void movement or change in void shape, or the void damage is too excessive. The measurement of the noise spectra combined with resistance-thermal modeling of the metal line during current flow was found to be able to predict the amount of voiding in the line.…”
Section: Introductionmentioning
confidence: 99%